- #1

superwolf

- 184

- 0

[tex]

L(x_1,...,x_n;p)=\Pi_{i=1}^{n}(\stackrel{n}{x_i}) p^{x_i}(1-p)^{n-x_i}

[/tex]

Correct so far?

The solution tells me to skip the [tex]\Pi[/tex]:

[tex]

L(x_1,...,x_n;p)=(\stackrel{n}{x}) p^{x}(1-p)^{n-x}

[/tex]

This is contradictory to all the examples in my book. Why?

L(x_1,...,x_n;p)=\Pi_{i=1}^{n}(\stackrel{n}{x_i}) p^{x_i}(1-p)^{n-x_i}

[/tex]

Correct so far?

The solution tells me to skip the [tex]\Pi[/tex]:

[tex]

L(x_1,...,x_n;p)=(\stackrel{n}{x}) p^{x}(1-p)^{n-x}

[/tex]

This is contradictory to all the examples in my book. Why?

Last edited: